Researching policy transfer of vocational education and training across the European Union : a systematic literature review - Ciantar, Maria [Verfasser] (My University, 2025)
“Various academic fields have focused on the transfer of Vocational Education and Training (VET) policies and practices, and the research base on VET policy transfer is broadly scattered. Recognising this deficit, researchers have sought to organise the current research. However, VET policy transfer studies carried out in European Union (EU) member states have made no such synthesising attempts. I conducted this systematic literature review to analyse the research methodology in this context. I searched for publications on the Scopus, Academic Search Ultimate (EBSCO), and ERIC databases, identifying a total of 577 publications, finding a total of 35 publications that met the inclusion criteria and that I subsequently analysed in detail. This review argues that research on VET policy transfer in the EU has particular gaps. It outlines four key areas that require attention: the lack of methodological diversity; the data collection from specific policy transfer actors and the exclusion of others; the geographical spaces that remain unexamined; and the focus on particular VET practices at the centre of policy transfer. The results identify lacunas in the current methodological practice of research on VET policy transfer in the EU and provide recommendations for future research.” (author’s abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; 370; Berufsbildung; Berufsbildungspolitik; Berufsbildungsforschung; Transfer; Europäische Union; Literaturanalyse